Facing metal stress by multiple strategies: morphophysiological responses of cardoon (Cynara cardunculus L.) grown in hydroponics - Sorrentino, Maria Cristina (Environ Sci Pollut Res Int, 2021)
The contamination of environments by heavy metals has become an urgent issue causing undesirable accumulations and severe damages to agricultural crops, especially cadmium and lead which are among the most widespread and dangerous metal pollutants worldwide. The selection of proper species is a crucial step in many plant-based restoration approaches; therefore, the aim of the present work was to check for early morphophysiological responsive traits in three cultivars of Cynara cardunculus (Sardo, Siciliano, and Spagnolo), helping to select the best performing cultivar for phytoremediation. For all three tested cultivars, our results indicate that cardoon displays some morphophysiological traits to face Cd and Pb pollution, particularly at the root morphology level, element uptake ability, and photosynthetic pigment content. Other traits show instead a cultivar-specific behavior; in fact, stomata plasticity, photosynthetic pattern, and antioxidant power provide different responses, but only Spagnolo cv. achieves a successful strategy attaining a real resilience to metal stress. The capacity of Spagnolo plants to modify leaf structural and physiological traits under heavy metal contamination to maintain high photosynthetic efficiency should be considered an elective trait for its use in contaminated environments. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s11356-021-13242-9.